Islamic Philanthropic: The Generosity of the Muhammadiyah Residents of Medan City during the Covid-19 Pandemic - Irfan, Irfan; Hani, Syafrida; Amal, Bakhrul Khair (Budapest International Research and Critics University, 2021)
This study aims to analyze the perceptions of Medan City Muhammadiyah residents about the economic burden of the community during the Covid-19 pandemic, as well as analyze the level of awareness of Medan City Muhammadiyah residents to pay zakat, infaq, alms and waqf to help the community's economic problems due to the Covid-19 pandemic. The survey design was conducted to collect data through a questionnaire (questionnaire) to 200 respondents who were analyzed using descriptive statistics. The results of the study found that the majority of Muhammadiyah residents agreed and had a high perception that the Covid-19 pandemic had caused an increase in the economic burden on the community during the Covid-19 pandemic. In addition, the majority of Muhammadiyah residents in Medan City have a very high level of awareness for tithing, infaq, charity and waqf in order to help the community's economic problems due to the Covid-19 pandemic.